White Emission from Li2O-BaO-Bi2O3-P2O5 Glass Doped with Dy3+ for Optical Condensed Material Applications - J. Tongdang; N. Chanthima; N. Kiwsakunkarn; Y. Tariwong; R. Rajaramakrishna; J. Kaewkhao; P. Limsuwan; C. Kedkaew (Integrated ferroelectrics, 2021)
Dy3+-doped lithium barium bismuth phosphate glasses were synthesized by the melt-quenching. The structural characteristics of the synthesized glasses were investigated by Fourier transform infrared (FTIR) spectroscopy. Symmetric and asymmetric vibrations of phosphorous oxygen groups were prominent bands in the FTIR spectra. Judd–Ofelt theory have been evaluated by the intensities of absorption bands in order to calculate oscillator strength (f). Luminescence intensity increases with increase in BaO content due to substitution of Ba2+ replacing Bi3+ which lead more void spaces providing enough space for Dy3+ ions to fit in. The branching ratio β parameter was distinguished to be maximum for the emission transition of 4F9/2 → 6H13/2 with the values of 0.59. LBBPDy glasses reveal an ideal warm white region when observed in CIE diagram. Our investigation reveals that the synthesized glasses may be utilized as a solid-state lighting material in various technological and industrial applications.
Keywords: Glass properties and applications; Luminescence Properties of Advanced Materials; Photorefractive and Nonlinear Optics